Authority of Taping as A Tool of Evidence in Criminal Acts of Corruption in Indonesia - S Franata, Hugo; Santiago, Faisal (Riviera Publishing, 2022)
Introduction: On the side of corruption crime, law enforcers are given special rights to obtain and access electronic information to strengthen evidence of corruption cases. The range of wiretapping on privacy related to human rights and its importance as electronic evidence in criminal acts of corruption, the purpose of this study is to examine wiretapping as evidence in criminal acts of corruption in Indonesia without violating constitutional rights. Methods: This research method uses normative jurisprudence with secondary data sources obtained through library research, including primary legal materials, secondary legal materials, and tertiary legal materials, both in the form of documents and regulations relating to wiretapping on corruption. At the same time, the data analysis technique used descriptive qualitative. Result: The principle of wiretapping is the legal basis of Law Number 19 of 2019; the law further explains legal certainty regarding granting permits to the Supervisory Board so that the KPK leadership can take immediate action. However, giving special keys to the apparatus must be balanced with caution to avoid misusing. Because the privileges granted intersect with the personal rights of every community, it is prone to human rights violations if it exceeds the limit / outside the problem of corruption. Conclusion: Law enforcement action against corruption gives special powers to law enforcers to obtain and use electronic information. The range of wiretapping on privacy related to human rights and the importance of such information as evidence of corruption must consider the applicable laws without violating constitutional rights.